KAJIAN POLA TATA BANGUNAN DAN LINGKUNGAN SERTA BENTUK BANGUNAN KAWASAN “THE REGATTA” DI PANTAI MUTIARA JAKARTA - HENDRA ADI PERMANA; PRAKARSA YOGA (Faktor Exacta, 2013)
Pattern of building and the environment and the form of the building will provide an area for the characteristics or identity forms and faces the city. According to Shirvani (1985), building linkages with the physical formation of urban space (urban space) lies in the composition of the future shape and pattern of the building. The Regatta is a multifunctional project consisting of 10 apartment towers, aqua park, hotel and serviced apartment which is built on an area of approximately 11 acres in Pearl Beach, Ancol, Jakarta. In accordance with the aim of structuring the superblock area Regatta, which became the new icon of the city of Jakarta, is expected to, become one of the exclusive residential and become a prime tourist spot in the city of Jakarta. Where the area of sustainable development and integrated into a need for local government in Jakarta. Untukitu deemed necessary to conduct this research with the aim of identifying the Spatial Pattern Affairs (Masterplan) and the Spatial Planning (Plan) at The Regatta Superblock area, identify the shape and look of the building The Regatta Superblock area and found the characteristic pattern of the building fabric and the environment and the form of the building The Regatta superblock area. The method used is to perform on-site observational study based on the theoretical basis used. Conclusion that in order to answer / address whether the approach to the concept of spatial development pattern area by Gordon Cullen, how the shape of the space between the building development area with the main theoretical approaches that Town Scape Gordon Cullen via Serial Vision and Place (Sequence, posession, and Content). Keyword: Patterns, building, area, regatta, beach pearl